2009
DOI: 10.1371/journal.pone.0007350
|View full text |Cite
|
Sign up to set email alerts
|

Human Sirt-1: Molecular Modeling and Structure-Function Relationships of an Unordered Protein

Abstract: BackgroundSirt-1 is a NAD+-dependent nuclear deacetylase of 747 residues that in mammals is involved in various important metabolic pathways, such as glucose metabolism and insulin secretion, and often works on many different metabolic substrates as a multifunctional protein. Sirt-1 down-regulates p53 activity, rising lifespan, and cell survival; it also deacetylases peroxisome proliferator-activated receptor-gamma (PPAR-γ) and its coactivator 1 alpha (PGC-1α), promoting lipid mobilization, positively regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 59 publications
3
51
0
1
Order By: Relevance
“…Since Sirtuin catalytic domains have been described as monomers [8,54], the Sirt1 termini might mediate oligomerization. Our experiments show, however, that Sirt1 is a monomer that migrates fast in SEC due to an extended conformation, apparently mainly due to a disordered N-terminus, consistent with bioinformatics analyses reported here and previously [55]. The C-terminus also appears to harbour disordered regions, but partially seems to adopt a defined conformation that interacts with the catalytic core [17].…”
Section: Discussionsupporting
confidence: 90%
“…Since Sirtuin catalytic domains have been described as monomers [8,54], the Sirt1 termini might mediate oligomerization. Our experiments show, however, that Sirt1 is a monomer that migrates fast in SEC due to an extended conformation, apparently mainly due to a disordered N-terminus, consistent with bioinformatics analyses reported here and previously [55]. The C-terminus also appears to harbour disordered regions, but partially seems to adopt a defined conformation that interacts with the catalytic core [17].…”
Section: Discussionsupporting
confidence: 90%
“…The structure of the catalytic domain of model sirtuins has been solved, 101 but computational methods applied to the full-length SIRT1 sequence indicate that the N-and C-terminal portions of the protein are largely unstructured, 102 which is an observation consistent with the idea that SIRT1 can interact with a vast array of different proteins by "coupled binding and folding. " Bioinformatic analysis of proteins found to contain large unstructured regions (designated intrinsically disordered proteins, or IDPs) has revealed that they are highly enriched in proteins that are network hubs.…”
Section: Sirt1 Is a Protein Network Hubmentioning
confidence: 84%
“…Human SirT1 consists of 747 amino acids, divided into four major regions: N-terminal domain (residues 1–182), allosteric site (residues 183–243), catalytic core (residues 244–498) and C-terminal domain (residues 499–747) (25). SirT1 catalyzes the protein deacetylation reaction in its catalytic core, which consists of two subdomains for NAD + and substrate binding (26).…”
Section: Discussionmentioning
confidence: 99%